(untitled) (Law, State and Telecommunications Review, 2019)
Purpose ”“ The join operations between data streams need more time and request more energy than traditional joins. In wireless sensor networks, energy is a critical factor. The survival of the network depends on this energy, thus it is necessary to consider, for this type of queries in such networks, the reduction of the sensors’ energy consumption. While works that have been done to treat n-way join operations between data streams are rare so far, we propose a technique, named NSLSJ (N-way Stream Local Semi-Join) to perform this type of join operations. The principal aim is to considerably reduce the consumed energy. Methodology/approach/design ”“ The technique ’N-way Stream Local Semi-Join (NSLSJ) proposed in this paper is based on an in-network execution, and on filtering tuples strategy for an important gain in energy. Findings ”“ Compared to NSLJ and Sens-Join techniques, NSLSJ shows better performances in the realized tests as it consumes less energy.